VARIABLE PRICING IN HOTEL INDUSTRY: A CASE STUDY FOR BUDGET HOTEL IN INDONESIA - , Alina Hasna Rasyanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The rising popularity of revenue management (RM) as a strategy to effectively allocate price and perishable resources nowadays is unquestionable. Relevant literatures in the context of RM are kept developing with their respective complexities, unexceptionally for hotel revenue management. However, not all of RM basic concepts could be applied to hotel industry, especially to budget hotels. Limited resource in advanced and integrated reservation system often hampers the process of recording booking request. This study therefore attempts to implement RM strategy in a more practical way through variable pricing, in a budget hotel in Yogyakarta, Indonesia. There are two customer segments involved in revenue calculation. The first segment is the group customer who dominates demand from January to June and from November to December, and the second one is business customer who dominates demand from July to October. Variable pricing is implemented to obtain the optimum price for each month whereas revenue is achieved from simulating several scenarios under various conditions. Comparison of all scenarios proves that employing variable pricing will provide better outcome, not only when executing it under current demand but also in the condition of stochastically generated demand. We also collect data from another hotel to prove that the models can be applied to other hotels with the same type. The result of this study should be a good reference for hotel decision maker in the future.